Compartmentalisation of Hepatitis B virus X gene evolution in hepatocellular carcinoma microenvironment and the genotype-phenotype correlation of tumorigenicity in HBV-related patients with hepatocellular carcinoma. Issue 1 (31st December 2022) - Fu, Ya; Fang, Fengling; Guo, Hongyan; Xiao, Xialin; Hu, Yuhai; Zeng, Yongbin; Chen, Tianbin; Wu, Songhang; Lin, Ni; Huang, Jinlan; Jiang, Ling; Ou, Qishui; et al.
ABSTRACT: Hepatitis B virus (HBV) exists as quasispecies (QS). However, the evolutionary characteristics of haplotypes of HBV X gene in the hepatocellular carcinoma (HCC) microenvironment remain unclear. Mutations across X gene are essential for the tumorigenicity of HBV X protein (HBx). However, the functional phenotypes of many mutant HBx remain unknown. This study aims to compare the characteristics of X gene evolution between tumour and non-tumour tissues in HCC patients and investigate the tumorigenic phenotype of HBx harbouring mutation T81P/S101P/L123S. This study included 24 HCC patients. Molecular cloning of X gene was performed to analyse characteristics of haplotypes in liver tissues. HCC cell lines stably expressing wild-type or mutant HBx and subcutaneous tumour xenograft mouse model were used to assess HBx-T81P/S101P/L123S tumorigenicity. The mean heterogeneity of HBV QS across X gene in tumour tissues was lower than that in non-tumour tissues. A location bias was observed in X gene clones with genotype C or D in tumour tissues compared to those with genotype B. Mutations in genotype-C or – D clones were mainly clustered in the dimerization region and aa110-aa140 within the transactivation region. A novel mutation combination at residues 81, 101 and 123 was identified in tumour tissues. Further, HBx-T81P/S101P/L123S promotes cell proliferation and increases genomic instability, which was mediated by MYC. This study elucidates the compartmentalized evolution patterns of HBV X gene between intra tumour and non-tumour tissues in HCC patients and provides a new mechanism underlying HBV-driven hepatocarcinogenesis, suggesting a potential viral marker for monitoring HCC.